PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA BANK SYARIAH - Pramesti Rihhadatul Aisy; St.Haelina Sefaringga; Asep supendi; Heny Saraswati; Wahyu Hidayat (Universitas Kristen Indonesia Toraja, 2023)
This research aims to find out how the influence of service quality on customer loyalty in Islamic banks. Service quality is represented by 6 variables, namely tangible, reliability, responsiveness, assurance, empathy and Compliance to Islamic Law. The research method used is a quantitative method which aims to find out the results of the data have been normally distributed. The data used in this study are primary data through questionnaires distributed to 30 respondents and secondary data to complete them. The results of this study are expected to increase the effectiveness of Islamic bank strategies in increasing the satisfaction of Islamic bank customers.